ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA INDUSTRI FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2012-2016 - Noor Rizky Setyowati, 14.05.52.0265; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2018)
This study aimed to examines the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), Total Asset Turn Over (TATO) and Earning Per Share (EPS) on the stock price. This research was conducted at Indonesia by using analysis unit pharmacy company that have gone public. The population of this research are pharmacy company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2012 until 2016 and obtained as many as 10 companies. The technique of data analysis is used multiple regression analysis. The results of this study shows that Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), Total Asset Turn Over (TATO)does not affect on stock price. Earning Per Share (EPS) significant positive influence on the stock price.Keyword: Current Ratio (CR), Debt to Asset Ratio (DER), Return on Asset (ROA), Total Asset Turn Over (TATO), Earning Per Share (EPS)and Stock Price.